Corps d’adeptes, paroles de Dieu et visions de Saints. Pratiques rituelles masculines et féminines dans deux sanctuaires de Tunis - Katia Boissevain (Revue des Mondes Musulmans et de la Méditerranée)
This article examines contemporary rituals practices by men and women in two sanctuaries of Tunis dedicated to Sayyida Manûbiyya, a woman saint of the 13th century. This ambivalent saint draws her religious legitimacy from two sources, scholarly sufism on one hand, through her affiliation to the Shâdhiliyya ṭarîqa, and a more popular side of sufism on the other. Both of these open up to different religious rituals, ḥaḍra for women, with possession dances, and dhikr sessions for men, followers of the Shâdhiliyya.However, one cannot conclude that relations between the body and the sacred are gender specific, with the feminine being more body oriented, while the masculine would be more intellectual. Both ceremonies engage the body fully in a dialogue with the sacred, while they find their ligitimacy in distinct sources, the Shâdhiliyya brotherhood for the dhikr, and the miraculous dimension of Khiḍr for the ḥaḍra.